2009
DOI: 10.1159/000209608
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of a Novel, Orally Active PDE4 Inhibitor

Abstract: Background: Intracellular cyclic adenosine monophosphate (cAMP) in inflammatory cells and airway smooth muscle is critical to the modulation of inflammatory response generation. Phosphodiesterase 4 (PDE4), an enzyme that catalyzes cAMP degradation, is therefore being actively explored as a molecular target for the treatment of airway inflammation, particularly asthma and chronic obstructive pulmonary disease. The field has undergone major advances in optimizing generation of compounds with a safe therapeutic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…7). These results for roflumilast and cilomilast were almost identical to those reported in a previous study using similar systems [30,31]. The glucocorticoid agent prednisolone has also been found to inhibit AHR in the same guinea pig model used in the present study [17].…”
Section: Discussionsupporting
confidence: 91%
“…7). These results for roflumilast and cilomilast were almost identical to those reported in a previous study using similar systems [30,31]. The glucocorticoid agent prednisolone has also been found to inhibit AHR in the same guinea pig model used in the present study [17].…”
Section: Discussionsupporting
confidence: 91%
“…Also, in human studies, SAP was unaffected by roflumilast treatment (Louw et al, 2007). On the other hand, an increase in cAMP levels inhibited the pro-inflammatory and apoptotic responses and provided an anti-inflammatory milieu (Dastidar et al, 2009;Naderi et al, 2009;Hoyle, 2010;Kim et al, 2010). So, it could be concluded that inhibition of PDE-4 reversed the hypertension-induced cognitive deficits independent of blood pressure.…”
Section: Discussionmentioning
confidence: 96%
“…While recent clinical evaluation of rolipram has been hampered by side effects of nausea and vomiting, a new generation of PDE4 inhibitors with a less adverse side effect profile is under evaluation (Dastidar et al, 2009;Davis et al, 2009). …”
Section: Phosphodiesterase Inhibitors (Rolipram)mentioning
confidence: 99%